Stigma Among Patients with HIV/AIDS: A Cross Sectional Study in Malaysia - Abdullah, Azreen; Ismail, Adibah Hanim; Mooi, Ching Siew (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction:HIV stigma refers to negative beliefs, feelings and attitudes towards people living with HIV (PLWH), groups associated with PLWH and other key populations at higher risk of HIV infection, such as people who inject drugs, sex workers, men who have sex with men and transgender people. Despite the advancement made in the knowledge and treatment of HIV, PLWH continues to be stigmatized. Objective: To determine the level of HIV stigma and its predictors among people living with HIV/AIDS in a tertiary hospital in Malaysia. Methods: A cross sectional study was conducted among HIV/AIDS patients aged 18 and above at infectious disease clinic in Hospital Sungai Buloh, Gombak, Malaysia. HIV stigma was assessed using Berger’s HIV stigma scale, which is available in Bahasa Malaysia and English.A self-administered questionnaire was used to determine their demographic and clinical characteristics. Multiple linear regression analysis was used to identify the predictors. Results: 526 subjects participated in this study. The mean age of the study population was 33.5± 8.4 years. The majority of the participants were male (90.9%) and contracted HIV through sexual activities (87.8%). The mean score of HIV stigma was 104.7 ± 19.5. Based on multiple linear regression analysis, patients who were unemployed (B = -8.00, 95% confidence interval (CI) = -12.12,-3.88, p = < 0.001) and being on antiretroviral treatment (B = 4.95, 95% (CI) = 0.30, 9.60, p = < 0.037) had higher level of HIV stigma. Conclusions: The level of HIV stigma was high (mean score =104.7 ± 19.5). HIV/AIDS patients who are unemployed and on antiretroviral agents were at risks of having higher level of HIV stigma. Future study is needed urgently to implement intervention that can minimize the stigmatization among patients with HIV/AIDS. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 26-35